Pemanfaatan Linktree Sebagai Solusi Masuknya Budaya Barat Terhadap Mahasiswa Dalam Perspektif Islam - Nur Afna Juanda; Viona Ratna Sariputri; Nishrina Syifa; Ani Nur Aeni (JIE (Journal of Islamic Education), 2022)
In this era of rapidly developing technology, the influence of foreign cultures such as western culture is entering Indonesia very quickly, especially among teenagers. The purpose of this study is to use the Linktree Website for students to understand the influence of western culture which is contrary to the Islamic perspective. While the benefits of this research are expected for students to be more careful in following western cultural trends in everyday life. This method uses Development and Design (D&D) with the ADDIE model which consists of going through the stages of analysis, design, development, implementation, and evaluation. At the analysis stage, teenagers who are easily attracted to outside cultures and are good at using technology are the background of this research. At the design stage, it was done by compiling content according to the results of observations and interviews on GoogleForm which was distributed to 30 students. At the development stage, content is included in YouTube videos and the results of product evaluations on Quiziz. This implementation stage links the product link on the Linktree website by testing it with students. The results of research on product trials to students resulted in 99% with effective qualifications in providing information. So it can be concluded that the use of technology by utilizing the Linktree website is effective in providing information on the influence of western culture which is contrary to Islamic.